Kualitas Sumber Daya Manusia Transportasi Laut Di Revolusi Industri 4.0 Menuju Era Pelabuhan Pintar - Aditya Mutiara Dewi; Fetiyana Hanty (Sekolah Tinggi Maritim Yogyakarta, 2022)
The marine transportation sector has entered the era of digitalization in line with the industrial revolution 4.0. The existence of the industrial revolution is caused by three main faktors, namely Technological Faktors, Economic Faktors and Socio-Cultural Faktors. The industrial revolution 4.0 focuses on the development of the digital world and the internet. Sea transportation is not only used for passenger transportation, but can also be used as transportation for the distribution of goods. Various companies have taken advantage of sea transportation for the process of sending logistics. Logistics delivery to different regions requires an effective and efficient transportation process. The purpose of this study is to find out the efforts made to improve Marine Transportation Human Resources. This research uses qualitative methods by collecting data through observation, reading orientation and interviews. This type of research is descriptive, namely research that describes information data based on reality (facts) obtained in the field. Efforts are made to improve the quality of Marine Transportation Human Resources towards the era of smart ports with formal and informal training in the field of port automation technology.